A case study of the financial benefits of a credit union's homeless prevention scheme. Issue 1 (2nd January 2020) - Lee, Bill; Carlisle, Liam
ABSTRACT: This paper examines the merits of homeless prevention loans offered by a credit union in the UK to the tenants of its housing association partners. Using a theoretical framework informed by the idea that social inclusion and social exclusion are multidimensional and dynamic, with each dimension impacting on all others, the paper examines the potential impact of loans of this type on both housing tenure and financial inclusion. The paper provides a rare case study of a credit union in the disciplines of accounting and financial management. IMPACT: This paper provides important insights for credit unions, housing associations and local councils. Local councils may work with credit unions to promote financial wellbeing for social housing tenants. People at risk of eviction appear to have a greater inability to repay loans than a credit union's regular membership. However, many recipients do repay loans and their repayments permit the credit union to help others who are also vulnerable to eviction. Spreading the cost of supporting people at risk of eviction through local authority grants to credit unions, or through local authorities' underwriting of losses created by such groups, provides a means to share the risk of financial initiatives that prevent housing exclusion and promote financial inclusion. The authors are an academic and a credit union manager who was previously a housing officer for a local council.